Method for producing efficient dephosphorizing agent for steelmaking from solid waste mixed material

By mixing OG mud and LT ash with rebate, white ash and greystone powder in a set proportion and sintered, a high alkaline dephosphorization agent is prepared, which solves the problems of low efficiency, high cost and environmental pollution in the traditional dephosphorization method. It achieves the effect of efficient phosphorus removal in steelmaking.

CN119464624APending Publication Date: 2025-02-18BEIJING SHOUGANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566445.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional dephosphorization methods are inefficient, costly and harmful to the environment, making it difficult to meet the needs of efficient phosphorus removal in steelmaking.

Method used

By mixing OG mud and LT ash at a set mass ratio, a solid waste mixing material is formed, and mixed with rebate, white ash and grey stone powder in a set proportion and then sintered, a dephosphorizer with high alkalinity is prepared.

Benefits of technology

The efficiency, economy and environmental protection of the dephosphorizer in the steelmaking process are achieved, and the plasticity and impact toughness of the steel are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464624A_ABST
    Figure CN119464624A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a steelmaking efficient dephosphorizing agent from solid waste mixed materials, and belongs to the field of ferrous metallurgy and solid waste resource utilization. The method comprises the following steps: mixing OG mud and LT ash according to a first set mass ratio to obtain a solid waste uniformly-mixed material; mixing the solid waste uniformly-mixed material with return mine, lime and limestone powder according to a second set mass ratio to obtain a mixture; and sintering the mixture to obtain the dephosphorizing agent. According to the method, resource utilization of solid wastes such as the OG mud and the LT ash is realized, and waste discharge and environmental pollution are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the fields of iron and steel metallurgy and resource utilization of solid waste, and in particular to a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture. Background Art

[0002] Phosphorus is a harmful element in most steel grades, which will significantly reduce the plasticity and impact toughness of steel. With the increasing demand for high-strength, high-toughness, and high-stress corrosion resistance steel grades and increasingly stringent quality requirements, countries around the world are working hard to reduce the phosphorus content in steel.

[0003] Traditional dephosphorization methods may face problems such as low dephosphorization efficiency, rising costs or adverse effects on the environment. Therefore, it is particularly important to develop an efficient, economical and environmentally friendly dephosphorization agent and its production method. Summary of the invention

[0004] The present application provides a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture, in order to solve the following technical problem: how to increase the basicity of the dephosphorization agent for steelmaking.

[0005] In a first aspect, the present application provides a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture, the method comprising:

[0006] The OG mud and the LT ash are mixed according to a first set mass ratio to obtain a solid waste mixed material;

[0007] The solid waste mixed material is mixed with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material;

[0008] The mixed material is sintered to obtain a dephosphorization agent.

[0009] Optionally, the first set mass ratio is m1:m2=(1-2):3, wherein m1 represents the mass of OG mud and m2 represents the mass of LT ash.

[0010] Optionally, the water content of the solid waste mixture is 8% to 14% by mass.

[0011] Optionally, in terms of mass fraction, the second set mass ratio is m3:m4:m5:m6=(20-55):(15-30):(4-8):(8-15), where m3 represents the mass of the solid waste mixed material, m4 represents the mass of the returned ore, m5 represents the mass of the lime, and m6 represents the mass of the limestone powder.

[0012] Optionally, the solid waste mixed material is mixed with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material, comprising:

[0013] The solid waste mixed material is mixed with the returned ore, lime, limestone powder and external ore according to a second set mass ratio to obtain a mixed material; wherein,

[0014] The second set mass ratio is m3:m4:m5:m6:m7=(20-55):(15-30):(4-8):(8-15):(0.1-40), wherein m3 represents the mass of the solid waste mixed material, m4 represents the mass of the returned ore, m5 represents the mass of the lime, m6 represents the mass of the limestone powder, and m7 represents the mass of the external ore.

[0015] Optionally, sintering the mixed material to obtain a dephosphorization agent comprises:

[0016] The mixture is sintered, and the carbon content of the mixture is adjusted in two stages to obtain a dephosphorization agent; wherein the carbon content of the mixture is adjusted to 2.95% to 3.35% in the first stage, and the carbon content of the mixture is adjusted to 3.05% to 3.45% in the second stage.

[0017] Optionally, the duration of the first stage is 9 minutes to 11 minutes.

[0018] Optionally, the sintering temperature is 1200°C to 1300°C.

[0019] Optionally, the sintering time is ≤12 hours.

[0020] In the second aspect, the present application provides a dephosphorization agent prepared by the method described in the first aspect, wherein the calcium ferrite content in the dephosphorization agent is ≥50% by mass, the FeO content of the dephosphorization agent is 7% to 9%, and the basicity of the dephosphorization agent is 3.0 to 4.5.

[0021] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0022] The present application provides a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture, the method comprising: mixing OG mud and LT ash according to a first set mass ratio to obtain a solid waste mixture; mixing the solid waste mixture with return ore, lime and limestone powder according to a second set mass ratio to obtain a mixture; sintering the mixture to obtain a dephosphorization agent. The solid waste mixture OG mud and LT ash contain rich iron oxide (Fe2O3, FeO) and alkaline oxides (such as CaO). During the high-temperature sintering process, the iron oxide and alkaline oxide in the mixture react to obtain a dephosphorization agent with a higher alkalinity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0025] Figure 1 A schematic flow chart of a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture provided in an embodiment of the present application. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0027] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0028] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0029] Figure 1 A schematic flow chart of a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture provided in an embodiment of the present application;

[0030] like Figure 1 As shown, the embodiment of the present application provides a method for producing an efficient dephosphorization agent for steelmaking from a solid waste mixture, comprising:

[0031] S1, mixing OG mud and LT ash according to a first set mass ratio to obtain a solid waste mixed material;

[0032] OG mud, the full name of which is converter OG mud, is a by-product produced by oxygen top-blown converter OG wet dust removal during the steelmaking process. OG mud contains high levels of calcium oxide (CaO), ferrous oxide (FeO) and other components, which are essential for dephosphorization reactions. OG mud also contains iron oxides (such as Fe2O3, Fe3O4), which help to form slag that is conducive to dephosphorization during the dephosphorization process. As a valuable secondary resource, OG mud has a high recycling value.

[0033] LT ash, or converter dry dust removal ash, is an important by-product produced during the steelmaking process. The main components of LT ash are Fe and Ca, and it also contains a small amount of solid C. It has the characteristics of fine particle size and high iron content. These characteristics make LT ash a recyclable secondary resource with high reuse value.

[0034] In some embodiments, the first set mass ratio is m1:m2=(1-2):3, wherein m1 represents the mass of OG mud, and m2 represents the mass of LT ash.

[0035] The positive effect of limiting the first set mass ratio to m1:m2=(1-2):3 is that a reasonable mixing ratio helps to optimize the physical and chemical properties of the dephosphorization agent, making it more stable and efficient during the dephosphorization process. On the other hand, this ratio can ensure normal moisture after mixing.

[0036] In some embodiments, the water content of the solid waste mixture is 8% to 14% by mass.

[0037] A moisture meter is installed on the conveyor belt of the solid waste mixture to ensure that the moisture content always remains within the optimal range.

[0038] The positive effect of limiting the moisture content of the solid waste mixed material to 8% to 14% is that if the moisture content of the solid waste mixed material is greater than 14%, it will cause the problem of sticking to the warehouse; if the moisture content is less than 8%, dust will be generated during the feeding process. Exemplarily, the moisture content of the solid waste mixed material can be 8%, 10%, 12%, 13%, 14%, etc.

[0039] S2, mixing the solid waste mixed material with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material;

[0040] In some embodiments, the second set mass ratio is m3:m4:m5:m6=(20-55):(15-30):(4-8):(8-15), wherein m3 represents the mass of the solid waste mixed material, m4 represents the mass of the returned ore, m5 represents the mass of the lime, and m6 represents the mass of the limestone powder.

[0041] In some embodiments, the solid waste mixed material is mixed with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material, including:

[0042] The solid waste mixed material is mixed with the returned ore, lime, limestone powder and external ore according to a second set mass ratio to obtain a mixed material; wherein,

[0043] The second set mass ratio is m3:m4:m5:m6:m7=(20-55):(15-30):(4-8):(8-15):(0.1-40), wherein m3 represents the mass of the solid waste mixed material, m4 represents the mass of the returned ore, m5 represents the mass of the lime, m6 represents the mass of the limestone powder, and m7 represents the mass of the external ore.

[0044] Certain components in the solid waste mixture (such as CaO in converter slag) can react with phosphorus at high temperatures to form phosphates, thereby achieving dephosphorization. The unqualified sintered ore produced during the sintering process is called return ore, and the return ore usually needs to re-enter the sintering process for reprocessing to improve resource utilization. The return ore contains certain liquid substances and incompletely sintered ore particles. Adding an appropriate amount can improve the particle size composition and structure of the sintered dephosphorization agent, thereby improving the quality of the sintered dephosphorization agent. White ash, its main chemical components include calcium oxide (CaO) and magnesium oxide (MgO). Limestone powder, its main component is calcium carbonate (CaCO3), is an important component in the dephosphorization agent. Adding an appropriate amount can provide enough calcium oxide to react with phosphorus in molten iron to form insoluble calcium phosphate, thereby improving the dephosphorization effect. External ores include PB powder, Mike powder and Baca powder. An appropriate amount of external ores can ensure that the proportions of various components in the sintered dephosphorization agent are moderate, which helps to form a stable mineral phase structure and liquid phase generation, thereby improving the overall quality of the sintered dephosphorization agent.

[0045] The second set mass ratio is m3:m4:m5:m6:m7=(20-55):(15-30):(4-8):(8-15):(0.1-40) with positive effects: in terms of mass ratio, when the solid waste mixed material is 20-55, the content of components in the solid waste mixed material is moderate, which can ensure sufficient dephosphorization capacity. In terms of mass ratio, when the added return ore is greater than 30, the permeability of the sintering material layer will deteriorate, affecting the transfer and distribution of heat, resulting in unstable sintering process, and even over-burning or under-burning. In terms of mass ratio, the addition of white ash less than 4 will lead to insufficient effective dephosphorization components in the dephosphorization agent, which cannot fully react with phosphorus in the molten iron to form insoluble compounds such as calcium phosphate, thereby reducing the dephosphorization effect. However, excessive white ash does not mean that the dephosphorization efficiency will continue to improve. In terms of mass ratio, the addition of white ash greater than 8 may lead to a relative reduction in the proportion of other effective dephosphorization components in the slag, which in turn reduces the overall dephosphorization effect. In addition, high white ash content will increase the heat consumption during the sintering process because more energy is required to decompose and react the excess white ash. This not only increases the production cost, but may also have a negative impact on the life and stability of the sintering machine. In terms of mass ratio, the addition of limestone powder greater than 15 may change the mineral composition and structure of the sintered ore, resulting in a decrease in the strength and density of the sintered ore, affecting blast furnace production. In terms of mass ratio, the addition of external ore greater than 40 may deteriorate the permeability during the sintering process, increase the difficulty of sintering and energy consumption. This is not conducive to the stable progress of the sintering process and the realization of energy conservation and emission reduction goals. Exemplarily, the second set mass ratio can be 20:15:4:8:0.1, 25:15:4:8:0.1, 30:16:5:9:5, 35:18:6:10:10, 40:20:7:11:20, 45:25:7.5:12:30, 55:30:4:15:40, etc.

[0046] S3, sintering the mixture to obtain a dephosphorization agent;

[0047] In some embodiments, sintering the mixed material to obtain a dephosphorization agent comprises:

[0048] The mixture is sintered, and the carbon content of the mixture is adjusted in two stages to obtain a dephosphorization agent; wherein the carbon content of the mixture is adjusted to 2.95% to 3.35% in the first stage, and the carbon content of the mixture is adjusted to 3.05% to 3.45% in the second stage.

[0049] There may be various unforeseen changes during the sintering process, such as fluctuations in the properties of raw materials, changes in sintering temperature, etc. The carbon content of sintering is adjusted in two stages, which can respond to these changes in a timely manner, ensure the stability of the sintering process and the quality of the sintering dephosphorization agent, and avoid a one-time large-scale adjustment that causes the sintering process to be out of control. Setting a lower carbon content range (2.95% to 3.35%) in the first stage helps to form a relatively stable solid phase skeleton in the early stage of sintering. A lower carbon content can reduce the amount of liquid phase generated during the sintering process, thereby avoiding premature liquid phase bonding that leads to a decrease in the permeability of the sintered body. This is conducive to the full contact between gas discharge and solid waste mixed materials during the sintering process, laying the foundation for subsequent sintering reactions. Exemplarily, the carbon content in the first stage can be 2.95%, 3.05%, 3.15%, 3.25%, 3.35%, etc.; when the sintering enters the second stage, the carbon content is appropriately increased to 3.05% to 3.45%, which can promote the generation of liquid phase during the sintering process. The presence of an appropriate amount of liquid phase helps further fusion and densification of particles in the solid waste mixture, and improves the strength and porosity of the dephosphorization agent. At the same time, the carbonaceous components in the liquid phase may also play a reducing role, which is conducive to removing impurity elements in the solid waste and improving the purity of the dephosphorization agent. Exemplarily, the carbon content in the second stage can be 3.05%, 3.15%, 3.25%, 3.35%, 3.45%, etc.

[0050] In some embodiments, the duration of the first stage is 9 minutes to 11 minutes.

[0051] The duration of the first stage is 9 minutes to 11 minutes, which is based on a large amount of experimental data and production experience. Entering the second stage for carbon adjustment after 9 minutes to 11 minutes can ensure that the sintering process obtains enough carbon at the appropriate stage to meet the needs of the subsequent high-temperature stage. At the same time, this time point also avoids the problems that may be caused by carbon adjustment too early or too late, such as insufficient liquid phase generation. Exemplarily, the duration of the first stage can be 9 minutes, 10 minutes, 11 minutes, etc.

[0052] In some embodiments, the sintering temperature is 1200°C to 1300°C.

[0053] Sintering temperature is one of the most important parameters in the sintering process, which directly affects the physical properties and chemical composition of the sintered product. High-temperature sintering helps the alkaline oxides (such as calcium oxide, magnesium oxide, etc.) in the solid waste mixture to fully fuse with other components to form a highly active dephosphorizing agent. These active ingredients can react with phosphorus in the molten steel faster during the steelmaking process to improve the dephosphorization efficiency. In addition, the appropriate sintering temperature can promote the optimization of the internal structure of the dephosphorizing agent, such as forming a porous structure or increasing the specific surface area, which are conducive to the full contact and reaction between the dephosphorizing agent and the molten steel, further improving the dephosphorization effect. Therefore, sintering in the range of 1200℃ to 1300℃ can ensure that the effective ingredients in the solid waste mixture react fully to form a stable compound, while avoiding too high a temperature causing the sintered body to melt or overburn, and too low a temperature causing incomplete sintering. Exemplarily, the sintering temperature can be 1200℃, 1220℃, 1240℃, 1260℃, 1280℃, 1300℃, etc.

[0054] In some embodiments, the sintering time is ≤ 12 hours.

[0055] The positive effect of limiting the sintering time to ≤ 12 hours is to avoid problems such as grate blockage and electric field dust accumulation caused by zinc load enrichment, which affect subsequent normal production. For example, the sintering time can be 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, etc.

[0056] In some embodiments, when the sintered dephosphorization agent reaches the tail of the machine, the carbon content of the mixture and the ratio of the solid waste mixed material can be adjusted according to the conditions of the tail section.

[0057] In the process of sintering dephosphorization agent, when the sintered dephosphorization agent reaches the tail of the machine, the situation of the tail section is an important feedback indicator, which directly reflects the progress of the sintering process and the quality of the sintered dephosphorization agent. By observing the tail section, the permeability, sintering degree, liquid phase generation amount of the sintered dephosphorization agent and whether there is over-burning or under-burning can be judged. When the sintered dephosphorization agent reaches the tail of the machine, if it is observed that the tail section has problems such as poor permeability, incomplete sintering or excessive liquid phase generation, it may be caused by inappropriate carbon content in the mixture. At this time, according to the specific situation of the tail section, the carbon content of the mixture can be appropriately adjusted. If the permeability is not good, it may be that the carbon content is too low, resulting in insufficient liquid phase generation. The carbon content can be appropriately increased to promote liquid phase generation; if the liquid phase is too much, the sintered dephosphorization agent is too soft or agglomerated, and the carbon content can be appropriately reduced to limit the liquid phase generation.

[0058] As one of the raw materials of the sintering dephosphorization agent, the ratio of the solid waste mixed material not only affects the cost of the dephosphorization agent, but also affects the performance and quality of the sintering dephosphorization agent. By adjusting the ratio of the solid waste mixed material, the production cost can be reduced and the recycling of resources can be realized under the premise of ensuring the quality of the dephosphorization agent. If the tail section shows that the quality of the sintered dephosphorization agent is stable, and the components in the solid waste mixed material have no adverse effect on the sintering process, it is possible to consider appropriately increasing the ratio of the solid waste mixed material to reduce the production cost. However, it should be noted that the increase in the ratio should be carried out gradually, and the quality changes of the sintered dephosphorization agent should be closely observed to avoid excessive ratios that lead to a decrease in the quality of the sintered dephosphorization agent. If the tail section shows that the sintered dephosphorization agent has certain quality problems (such as insufficient strength, excessive porosity, etc.), and these problems are related to the composition or ratio of the solid waste mixed material, then the ratio or composition of the solid waste mixed material should be adjusted accordingly to improve the quality of the sintered dephosphorization agent.

[0059] In a second aspect, the present application provides a dephosphorization agent prepared by the method described in the first aspect, wherein the calcium ferrite content in the dephosphorization agent is ≥50% by mass, and the FeO content of the dephosphorization agent is 7% to 9%.

[0060] As a highly efficient dephosphorization agent, calcium ferrite has a high content (≥50%), which means that it can provide stronger dephosphorization ability during the dephosphorization process. Calcium ferrite can react with phosphorus in molten steel to form stable phosphorus compounds, thereby effectively removing phosphorus from molten steel. In addition, calcium ferrite has good slag-forming properties. Its high melting point, low fluidity and good fluidity enable liquid slag to be quickly formed during the dephosphorization process, thereby improving the slag-forming conditions in the furnace. Good slag-forming conditions are conducive to the full contact and reaction between slag and molten steel, improving the efficiency of the dephosphorization reaction.

[0061] As an oxidant, FeO can improve the oxidizability of slag in the dephosphorization reaction, which is beneficial to the oxidation and removal of phosphorus. This is because phosphorus usually exists in the form of [P] in molten steel and needs to be converted into P2O5 through oxidation reaction, and then combined with the basic oxides in the slag to achieve dephosphorization.

[0062] During the steelmaking process, phosphorus is oxidized to P2O5 in molten iron. With the addition of a high-basicity dephosphorization agent, P2O5 combines with alkaline oxides such as CaO to form stable phosphates, thereby achieving efficient dephosphorization during the steelmaking process. In some embodiments, the basicity of the dephosphorization agent is 3.0 to 4.5.

[0063] The increase of basicity can increase the distribution coefficient of phosphorus, that is, promote the transfer of phosphorus from molten steel to slag. This means that in the dephosphorization process, higher basicity is conducive to the removal of phosphorus. On the other hand, under alkaline conditions, the oxidation reaction rate of phosphorus can be accelerated. The dephosphorization reaction is mainly phosphorus and the iron oxide (FeO) and alkaline oxide (such as CaO) in the slag to generate stable phosphates. Higher basicity can provide more alkaline oxides as reactants, thereby accelerating the dephosphorization reaction. The basicity of the dephosphorizing agent prepared in the embodiment of the present application can be 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.5, etc.

[0064] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0065] This embodiment provides a method for producing a steelmaking efficient dephosphorization agent from a solid waste mixture, comprising the following steps: mixing OG mud and LT ash according to a first set mass ratio to obtain a solid waste mixture;

[0066] The solid waste mixed material is mixed with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material;

[0067] The mixed material is sintered to obtain a dephosphorization agent.

[0068] The composition (wt%) of the mixture is shown in Table 1.

[0069] The sintering production process, the composition (wt%) and basicity of the dephosphorization agent are shown in Table 2.

[0070] Table 1 Composition of the mixture (wt%)

[0071] Group Solid waste mixing Foreign Minerals Return of ore White ash Limestone powder Example 1 23 42 19 7 9 Example 2 33 25 25 6 12 Example 3 37 15 29 4 15

[0072] Table 2 Sintering production process, dephosphorization agent composition (wt%) and basicity

[0073]

[0074] It can be seen from Tables 1-2 that the composition of the mixture and the sintering production process of the embodiment are both within the required range of the present invention. The produced dephosphorization agent has a calcium ferrite content of more than 50% and a FeO content of 7%-9%. Therefore, its dephosphorization and slag-making effects are better than those of existing dephosphorization agents.

[0075] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0076] 1. This application only uses about 7% of lime, and the rest is supplemented by limestone powder to produce dephosphorization agent, which significantly reduces the cost compared with other dephosphorization agents.

[0077] 2. Using OG mud and LT ash as the main materials, dephosphorization agent is produced on the existing sintering machine, achieving the dual benefits of steelmaking dephosphorization and cost reduction.

[0078] 3. Resource utilization of solid waste: OG mud and LT ash are solid wastes in the steelmaking process. If they are directly discharged or piled up, they will not only occupy land resources, but also pollute the environment. By converting these wastes into valuable steelmaking dephosphorization agents, the resource utilization of solid waste is achieved and environmental pollution is reduced.

[0079] 4. The dephosphorization agent produced in this application contains about 50% iron, which can increase the output of molten steel.

[0080] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A method for producing an efficient dephosphorization agent for steelmaking from solid waste mixed materials, characterized in that: The method comprises: The OG mud and the LT ash are mixed according to a first set mass ratio to obtain a solid waste mixed material; The solid waste mixed material is mixed with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material; The mixed material is sintered to obtain a dephosphorization agent.

2. The method according to claim 1, characterized in that: The first set mass ratio is m1:m2=(1-2):3, wherein m1 represents the mass of OG mud, and m2 represents the mass of LT ash.

3. The method according to claim 1, characterized in that Calculated by mass fraction, the moisture content of the solid waste mixture is 8% to 14%.

4. The method according to claim 1, characterized in that The second set mass ratio is m3:m4:m5:m6=(20-55):(15-30):(4-8):(8-15), wherein m3 represents the mass of the solid waste mixed material, m4 represents the mass of the returned ore, m5 represents the mass of the lime, and m6 represents the mass of the limestone powder.

5. The method according to claim 1, characterized in that The solid waste mixed material is mixed with the returned ore, lime and limestone powder according to a second set mass ratio to obtain a mixed material, comprising: The solid waste mixed material is mixed with the returned ore, lime, limestone powder and external ore according to a second set mass ratio to obtain a mixed material; wherein, The second set mass ratio is m3:m4:m5:m6:m7=(20-55):(15-30):(4-8):(8-15):(0.1-40), wherein m3 represents the mass of the solid waste mixed material, m4 represents the mass of the returned ore, m5 represents the mass of the lime, m6 represents the mass of the limestone powder, and m7 represents the mass of the external ore.

6. The method according to claim 1, characterized in that The method of sintering the mixed material to obtain a dephosphorizing agent comprises: The mixture is sintered, and the carbon content of the mixture is adjusted in two stages to obtain a dephosphorization agent; wherein the carbon content of the mixture is adjusted to 2.95% to 3.35% in the first stage, and the carbon content of the mixture is adjusted to 3.05% to 3.45% in the second stage.

7. The method according to claim 6, characterized in that The duration of the first stage is 9 minutes to 11 minutes.

8. The method according to claim 1 or 6, characterized in that: The sintering temperature is 1200°C to 1300°C.

9. The method according to claim 8, characterized in that The sintering time is ≤12 hours.

10. A dephosphorization agent prepared by the method according to any one of claims 1 to 9, characterized in that: Calculated by mass fraction, the calcium ferrite content of the dephosphorization agent is ≥50%, the FeO content of the dephosphorization agent is 7% to 9%, and the basicity of the dephosphorization agent is 3.0 to 4.5.